Biomass- and coke oven gas based methanol production - Asp, Björn (2007)
This study considers production of methanol as a motor fuel, generated from coke oven gas at the steel mill SSAB Tunnplåt in Luleå. In addition, different systems with a biomass gasification plant included are considered. The produced synthesis gas is mixed with the coke oven gas to enhance the methanol production. Different technologies for production of the alcohol are applied. The selected techniques are based upon their advantageous by economical and technical characteristics. The selected systems are modelled in Aspen plus, which is a widely used process simulation software. The resulting dimensions of streams, units and the energy balances are subsequently used for the economic analysis. Global warming caused by an increased concentration of greenhouse gases is of major concern today. It is predicted that global warming will cause sea level rise and other environmental impacts that may harm humans and nature. The significant increase of greenhouse gases over the last 200 years is almost entirely due to human activities and particularly due to combustion of fossil fuels. By using biomass as fuel for production of methanol as motor fuel, it would contribute to decrease the total green house gas emission level. The coke oven gas which origins from fossil based coal, could be used in a better manner as fuel for methanol production than for increase the present electricity production at LULEKRAFT AB (LUKAB). That is because the methanol production leads to a product with lower specific CO2 emissions due to that the conversion- and total plant efficiency are much higher. The wood-pellets produced from sawdust at Bioenergi are to a large extent exported from the county to heat and power plants, which purchase the pellets to a low price. A better option would be to use the sawdust for methanol production, which would be more profitable and could be used within the county and thereby also minimize the transportation costs and green house gas emissions. The conclusion is that methanol produced from 400 GWh coke oven ...